Glycyrrhizic acid delivery system Chitosan-coated liposome as an adhesive anti-inflammation: Glycyrrhizic acid delivery system Chitosan-coated liposome - Naseriyeh , Tahereh; Kahrizi, Danial; Alvandi, Hosna; Aghaz, Faranak; Nowroozi, Ghazal; Shamsi, Alireza; Hosseini, Omid; Arkan, Elham (Cellular and Molecular Biology, 2023)
Nowadays, medicinal plants are used to overcome the side effects of prescription drugs in modern medicine. Glycyrrhizic acid (GA) derived from the root of the licorice plant is one of the plant compounds whose effectiveness has been confirmed in the treatment of inflammatory bowel disorders (IBD). Liposome thin film hydration method was used to synthesize chitosan-coated liposomes containing GA. In the present study, chitosan-coated liposome was characterized by dynamic light scattering (DLS), zeta potential, scanning electron microscope (SEM) and Fourier transforms infrared spectroscopy (FTIR). The FTIR spectrum confirmed the coating of liposomes by chitosan polymer. Liposome coating leads to an increase in the size and values of zeta potential. The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay of chitosan-coated liposomes containing GA confirmed that it has no cytotoxicity toward fibroblasts cell line, therefore confirming their cytocompatibility. Overall, drug loading, release and cytotoxicity were evaluated and it was found that chitosan decreased the release rate of GA. It seems; chitosan-coated liposomes may be a suitable system for delivering liposomal GA in the treatment of IBD.